DUKUNGAN KELUARGA DENGAN KEPATUHAN PEMBATASAN CAIRAN PADA PASIEN GAGAL GINJAL KRONIK DENGAN HEMODIALISA - Puji Astuti; Abdul Ghofar; Edi Wibowo Suwandi (Universitas Pesantren Tinggi Darul Ulum, 2017)
ABSTRACTBackground: fluid restriction compliance is one of the problems in patients with chronic renal failure with hemodialysis therapy. Neither compliance can lead to treatment failure that can ultimately decrease the patient's quality of life and increase morbidity and mortality. Family support is crucial in determining confidence, a treatment program that helps patients to adhere to fluid intake restrictions. Objective: To Know Relation Family Support With Compliance Fluid Restriction In Chronic Kidney Failure Patients With Hemodialysis Therapy In Jombang General Hospital.Method: The study design was cross sectional with 45 respondent sample and used consecutive sampling method. Data collection was done with quizener and observation.Results: Most family support was good (77.8%) and adherence to partial high fluid intake restriction (605). There was a significant relationship between the two variables with p: 0,000 and r: 0.542 with moderate strength and positive direction, The higher the family support the higher the compliance rate of fluid restriction.Conclusions: There was a significant association between family support and adherence to fluid intake restriction on patients with chronic renal failure with hemodialysis therapy. Keywords: family support, compliance fluid restriction